FAKTOR PENGUAT DALAM IMPLEMENTASI KEBIJAKAN KAWASAN TANPA ROKOK DI INSTANSI KANTOR WALIKOTA JAYAPURA - Widyawati Widyawati (JURNAL KEBIJAKAN PUBLIK, 2020)
This article aims to analyze the Strengthening Factors in Implementing Non-Smoking Area Policy in Jayapura City Government Agencies. This type of research is a qualitative descriptive study with the focus of research analyzing the Strengthening Factors in the Implementation of the No Smoking Area Policy in Jayapura City Government Agencies, which consists of organizational appeals, internal supervision and application of sanctions. Data was collected through interviews with key informants as well as the Law Enforcement Team for Non-Smoking Regional Regulations (KTR Regional Regulations). Data analysis consists of the stages of Data Condensation, Data Display and Conclusion Drawing / Verifications. The results showed that based on the reinforcing factor, the Agency that violated the KTR Regional Regulation only received SP1 or SP2, no sanctions had yet been applied in the form of imprisonment for a maximum of three months or administrative fines as stated in the Jayapura City Regulation No. 7 of 2009 concerning No Smoking Area